Fauna of Langkawi Mangrove Forests - A, Sasekumar,; A.L, Ooi, (Malaysian Journal of Science, 2005)
The mangrove forests in the north-eastern part of Langkawi island are dominated by Rhizophora apiculata and Ceriops tagal, and cover an area of 1,987 ha that is drained by three major rivers, namely, Sg. Kisap, Sg. Air Hangat and Sg. Kilim. The tree canopy are home of a variety of birds, bats, monkeys and large number insects. The forest floor is colonized by a large variety of benthic invertebrates that live on the sediment surface, within the sediment as well as on the lower trunks of trees. These include 16 species of crustaceans (brachyuran crabs from the families Ocypodidae and Grapsidae) and 12 species of gastropods (Ellobiidae, Cerithididae and Littorinidae). These invertebrates play an important role in the ecology of the mangrove forests, by consuming organic matter and recycling nutrients. The conservation of these mangrove forests is vital for the existence of coastal fisheries, and marine life in the coastal waters of Langkawi.